(untitled) (Journal of Management, 2022)
Employee satisfaction is essential for an organization’s success and survival. Job satisfaction measures how happy workforces are with their jobs and working environment. Many factors involve improving or maintaining high satisfaction rates, which wise insurance sectors would do well to implement. Employees’ job satisfaction is a multi-disciplinary concept that results from their perception of their jobs and the degree to which a good fit exists between them and the insurance sector. This study aims to examine the relationship between job satisfaction dimensions and employee performance, and it also explores how satisfaction influences employee performance in life insurance sectors. Descriptive and causal-comparative research designs were employed to examine the relationship and explore the dimensions. Data have been gathered from the 240 respondents through stratified sampling techniques and entered into SPSS version 20 for the analysis. The correlation result of the study clarified that there was a positive and significant relationship between job satisfaction constructs and employee performance. As per regression analysis, payroll had a higher influence on job performance than other factors and was positively significant. So, the payroll system affected employees satisfaction to increase their performances. It has also reported significant positive relationships between interpersonal relationships and employee performance. However, there was an insignificant relationship between working environment and job performance.